Construction and optimization of the digital marketing ecosystem for Baijiu enterprises: A case study of Kweichow Moutai Group - TIAN Wuxu, TONG Jun (Zhongguo niangzao)
With the rapid development of digital economy, the traditional marketing model of Baijiu enterprises has been difficult to meet the needs of consumers in the new era. Facing the digital wave, the Baijiu industry has explored digital transformation to enhance brand influence and market competitiveness. The current digital marketing status and existing problems of Moutai Group was analyzed by sorting out digital transformation theory, customer relationship management theory and market positioning theory. The path was proposed to build and optimize the digital marketing ecosystem, including the construction of digital content production, management and operation ecology, as well as the implementation of safeguard measures. The research results had important practical significance and theoretical value to the digital transformation of Moutai Group and the whole Baijiu industry.